ANALISIS KEANGGOTAAN PETANI DALAM KELOMPOK TANI : STUDI KASUS KELOMPOK PEMBUDIDAYA IKAN “ULAM SARI” DESA KALIKIDANG, SOKARAJA, BANYUMAS - Neni Safitri; Istiqomah Istiqomah; Neni Widyaningsih; Sodik Dwi Purnomo (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2020)
Farmer groups become one of the agricultural institutions that have an important role in agricultural development. This study aims to analyze the effect of turnover, education level, length of business, and landholding on the membership of farmers in farmer groups and to analyze the variable that has the greatest effect on farmer membership. Stratified proportionate random sampling is used to select 34 farmers who join farmer group and 51 farmers who do not join farmer group. Stratification is based on landholding. The method used is logistic regression and Mann Whitney analysis using SPSS. The results show that turnover, education level, and landholding significantly influence farmer’s membership. Landholding has the biggest effect on the membership of farmers in farmer groups. Keywords: Agricultural institution, farmer group, farmer membership